Analysis of the correlation between the serum residual cholesterol level at admission and the risk of death after discharge in patients with ischemic stroke: Serum residual cholesterol level in ischemic stroke - Xu, De; Duan, Ruijuan; Zhu, Ruiqi; Huang, Yinghua; Chen, Shiyu (Journal of Medical Biochemistry, 2025)
[Objective] To investigate the relationship between residual cholesterol (RC) levels at admission and the risk of death after discharge in patients with ischemic stroke (IS).[Methods] A total of 2021 IS patients aged 35-80 years were selected as the study objects, and death endpoint data after discharge were collected. Restricted cubic spline (RCS) regression was used to analyze the dose‒response relationship between the RC at admission and the risk of death. The hazard ratio (HR) and 95% CI were calculated via Cox regression to analyze the association between the RC level at admission and the risk of death after discharge in patients with IS.[Results] According to the RCS model, RC levels were nonlinearly associated with deaths from IS and other causes (P
Keywords: Ischemic stroke; Blood lipid level; Residual cholesterol; Risk of death; Serum residual cholesterol level